The Role of Job Demands in Digital Human Resource Management: A Systematic Literature Review - Danar Tri Hartanto; Agung Wahyu Handaru; Achmad Fauzi; Kurniawan Prambudi Utomo (Journal of Business and Behavioural Entrepreneurship, 2026)
Digital transformation has encouraged organizations to implement Digital Human Resource Management (Digital HRM) to improve the effectiveness of human resource management. However, the implementation of Digital HRM also increases job demands, such as time pressure, job complexity, and the need to adapt to digital technologies. This study aims to analyze the relationship between job demands and Digital HRM and to identify research gaps within organizational and SME contexts. The study employed a systematic literature review (SLR) using a structured review approach. Articles were collected from reputable international databases, including Scopus, ScienceDirect, Emerald, Springer, Wiley, Taylor & Francis, SAGE, and Google Scholar covering the period 2020–2026. The selection process followed the PRISMA framework and resulted in 70 articles that met the inclusion criteria. Data were analyzed using descriptive and thematic approaches. The findings indicate that job demands are a critical factor influencing the effectiveness of Digital HRM implementation. High job demands may increase psychological pressure, burnout, and employee resistance toward digital systems when not supported by adequate organizational support. Conversely, digital training, managerial support, and technological infrastructure contribute positively to the successful implementation of Digital HRM. This study highlights the importance of managing job demands to support sustainable digital HR transformation, particularly in SMEs.